High Emotion Differentiation Buffers Against Internalizing Symptoms Following Exposure to Stressful Life Events in Adolescence: An Intensive Longitudinal Study. (July 2021) - Nook, Erik C.; Flournoy, John C.; Rodman, Alexandra M.; Mair, Patrick; McLaughlin, Katie A.
Exposure to stressful life events is strongly associated with internalizing psychopathology, and identifying factors that reduce vulnerability to stress-related internalizing problems is critical for development of early interventions. Drawing on research from affective science, we tested whether high emotion differentiation—the ability to specifically identify one's feelings—buffers adolescents from developing internalizing symptoms when exposed to stress. Thirty adolescents completed a laboratory measure of emotion differentiation before an intensive yearlong longitudinal study in which exposure to stress and internalizing problems were assessed at both the moment level ( n = 4, 921 experience-sampling assessments) and month level ( n = 355 monthly assessments). High negative and positive emotion differentiation attenuated moment-level coupling between perceived stress and feelings of depression, and high negative emotion differentiation eliminated month-level associations between stressful life events and anxiety symptoms. These results suggest that high emotion differentiation buffers adolescents against anxiety and depression in the face of stress, perhaps by facilitating adaptive emotion regulation.